BUILDING ADAPTIVE CURRICULUM MODELS WITH AI: INNOVATIONS AND IMPLICATIONS FOR TEACHING AND LEARNING - Dame Siregar; Zain Nizam; Syafiq Amir (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia, 2026)
The integration of artificial intelligence (AI) into education is rapidly transforming traditional curriculum models, offering new opportunities for personalized learning. AI-powered adaptive curriculum models have the potential to provide real-time, personalized learning experiences that cater to individual student needs. This study explores the role of AI in developing adaptive curricula and its impact on teaching and learning processes. The research aims to evaluate the effectiveness of AI-driven adaptive curriculum models in improving student engagement, academic performance, and overall learning outcomes. A mixed-methods approach was used, combining quantitative assessments of student performance with qualitative feedback from both students and teachers. The findings indicate that students in AI-powered learning environments exhibited a 20% improvement in academic outcomes and a 25% increase in engagement compared to students using traditional curricula. Additionally, teachers reported positive feedback regarding the adaptability and effectiveness of AI tools in addressing diverse student needs. The study concludes that AI-enhanced adaptive curriculum models offer significant potential for improving educational practices by providing more personalized, dynamic, and engaging learning experiences. Future research should explore the long-term impacts of AI-driven curricula and address ethical concerns related to data privacy and algorithmic biases.